Memahami Konsep “The Dream Society” oleh Rolf Jensen: Kebutuhan Emosional sebagai Prioritas Utama - Safitri, Dian (Jurnal Pendidikan Transformatif, 2023)
The purpose of this study was to find out the concept of "The Dream Society" by Rolf Jensen from the Rhenald Kasali Youtube channel entitled "Welcome to A Dream Society". In this study, the researcher used a qualitative approach with the note-taking method because the data source that the author obtained was through listening. The results of a brief review of the listening process explain that In a Dream Society, emotional needs will become a top priority and people will focus more on developing their skills and talents. Work will be a way to achieve a greater purpose in life, and individuals will be more committed to fighting for human rights, the environment, and social justice. More subtle values ​​such as beauty, creativity, and imagination will be highly valued. Products and services will be developed to meet emotional and aesthetic needs, and people will choose products that convey positive messages and evoke pleasant feelings.